Integrated Transcriptome and Metabolomics Analysis Reveals That Probiotics and Tea Polyphenols Synergetically Regulate Lipid Metabolism in Laying Hens - Ming Qin; Cai Ma; Zengguang Wang; Mingzhi Liang; Yufen Sha; Jiewei Liu; Shunjin Ge; Longzong Guo; Ruili Li (Agriculture)
Tea polyphenols (TP) and probiotics (PB) have been recognized for their ability to improve lipid metabolism and regulate immune function. However, their specific impact on lipid metabolism in laying hens has not been thoroughly elucidated. Therefore, this study sought to examine the effect of TP and Bacillus subtilis on lipid metabolism in laying hens through transcriptome and metabolome analyses. Two hundred Hy-line Brown layers were randomly allocated into four groups with supplemental dietary TP and PB alone and their combination for 8 weeks. Each treatment had 10 replicates of five birds. Supplementation with a TP and PB combination (TP-PB) increased redness (a*) (p < 0.05) compared to the control basal diet (CT). Dietary TP-PB decreased egg yolk and serum total cholesterol (TC) concentrations (p < 0.05) without affecting the content of total bile acid (TBA). The combined use of TP and PB significantly improved hepatic fatty acid synthetase (FAS) activity (p < 0.05) and reduced liver fat particles. Dietary TP-PB primarily influenced the transcript levels of genes involved in fat metabolic pathways. In particular, TP-PB supplementation reduced lipid storage by activating the Notch signaling pathway. Furthermore, the addition of TP-PB in the diet modulated the abundance of metabolic biomarkers associated with bile secretion and valine, leucine, and isoleucine degradation. An interaction network of mRNAs and metabolites was constructed associated with lipid metabolism, such as deoxycholic acid, TAG (14:3–14:3–20:5), PDK4, and HES4. Overall, these findings emphasized the potential health advantages of the TP and PB combination as a possible functional feed supplement in livestock nutrition.